The N‐Terminal Domain of ALS‐Linked TDP‐43 Assembles without Misfolding. Issue 41 (5th September 2017) - Tsoi, Phoebe S.; Choi, Kyoung‐Jae; Leonard, Paul G.; Sizovs, Antons; Moosa, Mahdi Muhammad; MacKenzie, Kevin R.; Ferreon, Josephine C.; Ferreon, Allan Chris M.
Abstract: Transactivation response element (TAR) DNA‐binding protein 43 (TDP‐43) misfolding is implicated in several neurodegenerative diseases characterized by aggregated protein inclusions. Misfolding is believed to be mediated by both the N‐ and C‐terminus of TDP‐43; however, the mechanistic basis of the contribution of individual domains in the process remained elusive. Here, using single‐molecule fluorescence and ensemble biophysical techniques, and a wide range of pH and temperature conditions, we show that TDP‐43 NTD is thermodynamically stable, well‐folded and undergoes reversible oligomerization. We propose that, in full‐length TDP‐43, association between folded N‐terminal domains enhances the propensity of the intrinsically unfolded C‐terminal domains to drive pathological aggregation. Abstract : Misfolding not included : The folded TDP‐43 N‐terminal domain facilitates C‐terminal domain‐dominated supramolecular protein assembly and pathologic aggregation with implications in several neurodegenerative diseases. Single‐molecule fluorescence and ensemble biophysical techniques were applied to elucidate the mechanistic basis of the assembly process.